PENGARUH KINERJA FINANSIAL PERUSAHAAN TERHADAP PENGUNGKAPAN SUSTAINABILITY REPORTING DAN SEBALIKNYA (Studi pada Perusahaan yang Mengeluarkan Sustainability Reporting dengan Kegiatan Usahanya di Bidang dan/atau Berkaitan dengan Sumber Daya Alam) - Arjuna Axellaudi S.R; Aditya Septiani (Diponegoro Journal of Accounting, 2022)
The problem that arises from the disclosure of sustainability reports in Indonesia is that not many companies are willing to disclose. So that in this case a bi-directional approach is used in the variables of sustainability reporting and the company's financial performance. The purpose of this study was to analyze the effect of the company's financial performance on the disclosure of sustainability reporting and the effect of the disclosure of sustainability reporting on the company's financial performance. The population selected in this study are companies that publish sustainability reporting according to the 2015-2019 period. The number of samples used in this study were 12 companies that published sustainability reporting according to the 2015-2019 period. The sampling technique in this research is purposive sampling method. The method of data collection is by using a questionnaire. The data analysis method used is multiple linear regression. Based on the research, financial performance has no significant effect on the disclosure of sustainability reporting. Disclosure of sustainability reporting has no significant effect on financial performance.